Analysis of Consumer Buying Behavior at the East Bekasi Regional Pharmacy - Leonard Parsaoran, Edward; Hartono , Sri (Journal of World Science, 2023)
This research is motivated by consumer behavior patterns in purchasing medicine at pharmacies. The variables used in this study include price, service quality, purchase decisions, and consumer trust as a mediator. The purpose of this research is to understand and analyze consumer purchasing behavior of medicine at pharmacies in the East Bekasi area. The methodology employed in this study is quantitative research with causal explanation. Data collection techniques involve distributing questionnaires. Meanwhile, the sampling technique utilizes a non-probability sampling design with purposive sampling. Data processing involves Structural Equation Modeling (SEM) using the SmartPLS software version 3.3.7 and includes 138 respondents. Based on the testing and analysis results, it can be concluded that consumer trust mediates price and service quality, consequently exerting a positive and significant influence on the purchase decisions of medicine at East Bekasi Pharmacy. The implications of this research are expected to contribute as information for entrepreneurs and managerial implications that can be practically applied within companies, particularly in determining marketing strategies by managing internal and external factors to enhance sales. Moreover, it also holds theoretical implications in the academic field with the hope of generating new theories.